Neonatal Hemolytic Jaundice: Causes, Diagnostic Approach, and Management - Stavroula Parastatidou; Andreas G. Tsantes; Chrysoula-Christina Emmanouil; Aikaterini Konstantinidi; Anastasia Kapetanaki; Rozeta Sokou (Children, 2025)
Neonatal jaundice remains a common issue in daily clinical practice that needs to be distinguished in physiologic and pathologic hyperbilirubinemia. Hemolytic causes are significant, often underrecognized contributors of pathologic hyperbilirubinemia, sometimes leading to severe complications. Both immune-mediated and non-immune hemolytic conditions are included in the differential diagnosis of neonatal hemolytic jaundice. Following the detection of hemolysis, family and pregnancy history, physical examination of the neonate, and further investigations are necessary. Established and newer laboratory methods are useful in the subsequent diagnostic approach. The optimal management of hemolytic jaundice alienates the risk of permanent neurologic damage.